Microstructural Effects between AHSS Dissimilar Joints Using MIG and TIG Welding Process. Issue 1766 (2015) - Medina, G.Y. Pérez; Padovani, M.; Merlin, M.; Pérez, A.F. Miranda; Valdés, F.A. Reyes
ABSTRACT: Gas tungsten arc welding-tungsten inert gas (GTAW-TIG) is focused in literature as an alternative choice for joining high strength low alloy steels; this study is performed to compare the differences between gas metal arc welding-metal inert gas (GMAW-MIG) and GTAW welding processes. The aim of this study is to characterize microstructure of dissimilar transformation induced plasticity steels (TRIP) and martensitic welded joints by GMAW and GTAW welding processes. It was found that GMAW process lead to relatively high hardness in the HAZ of TRIP steel, indicating that the resultant microstructure was martensite. In the fusion zone (FZ), a mixture of phases consisting of bainite, ferrite and small areas of martensite were present. Similar phase's mixtures were found in FZ of GTAW process. The presence of these mixtures of phases did not result in mechanical degradation when the GTAW samples were tested in lap shear tensile testing as the fracture occurred in the heat affected zone. In order to achieve light weight these result are benefits which is applied an autogenous process, where it was shown that without additional weight the out coming welding resulted in a high quality bead with homogeneous mechanical properties and a ductile morphology on the fracture surface. Scanning electron microscopy (SEM) was employed to obtain information about the specimens that provided evidence of ductile morphology.